THE EFFECT OF EDUCATIONAL VIDEOS AS AN EFFORT TO IMPROVE THERAPY SUCCESS USING THE HEALTH BELIEF MODEL APPROACH: PERCEPTION OF SEVERITY - Sundari, Trias Kania; Rajab, Muhammad Andy; Mukaromah, Diyana Latifatul; Afidah, Malikatul; Kamiela, Annisa Azkiya; Sulistyaningrum, Indriyati Hadi (Jurnal Farmasi Sains dan Praktis, 2026)
Patient compliance with hypertension treatment is often a problem in therapy, so pharmacists and other health workers need to make an effort to improve patients' understanding of the disease and complications that can occur when patients do not take their medication, in order to achieve the clinical outcome of controlled blood pressure. This study aims to determine the effect of educational videos accompanied by the health belief model component of perceived severity on the compliance of hypertensive patients at the Gayamsari Community Health Center in Semarang. The method used in this study was a quasi-experiment using a pre-test and post-test group control conducted on 52 samples of Prolanis Hypertension patients who met the inclusion criteria at the Gayamsari Community Health Center in Semarang City, who were given the MARS (Medication Adherence Rate Scale) questionnaire. Results: From the intervention group that received educational videos accompanied by the health belief model component of perceived severity, the Wilcoxon signed rank test results had a p-value of 0.001, which means that there was a difference in patient compliance scores between the pretest and posttest. Meanwhile, the difference in post-test results between the two groups (control and intervention) also showed significance in the Mann-Whitney U Test with a p-value of 0.000, meaning that educational videos with health belief model components can influence the adherence of hypertensive patients at the Gayamsari Community Health Center in Semarang City. Conclusion: Showing educational videos accompanied by health belief model components to hypertensive patients at the Gayamsari Community Health Center in Semarang City can significantly influence patient compliance with p<0.05.